IKRAR LAMTEH DAN PERGURUAN TINGGI ISLAM DI KOPELMA DARUSSALAM - Inayatillah Inayatillah (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2022)
One of the tangible results of implementing the points of the Lamteh Pledge is the establishment of a Darussalam education complex with two Islamic universities and one public university. This article will then examine aspects of the role of the lamteh pledge and how the development of the three universities in the education complex will be. Using the descriptive-analytic method on historical literature found several research results including. First, the main point of the Lamteh Pledge regarding religion, development, and prosperity has the same breath in education development. Second, Darussalam is a legendary achievement from a pledge that has so far revealed the joints of Acehnese people's lives. Third, Islamic universities in Darussalam have become the